Improving HOTS Literacy Using the PjBL Model with Crossword Puzzle Media on Reaction Rate Materials - Marpaung, Christine Petricia; Suyanti, Retno Dwi (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
Every student is required to master science literacy in social life because this literacy is related to the ability of students to relate issues about science and their ideas as citizens. The logical influence of the demands of teacher professionalism in the presentation of chemistry learning is the teacher's ability to create the right learning strategy in accordance with the problems faced in the world of education. One of the things that can be done in solving the problem in question is to transfer the old learning method with the new one. This study aims to determine the improvement of HOTS literacy by integrating the PjBL model with the Crossword Puzzle media on the Reaction Rate material in class XI SMA and to describe the most developed aspects of HOTS literacy. This research is a Quantitative Descriptive research using an experimental method with a One-Group Pretest-Posttest Design design. The results showed that students' HOTS literacy ability increased through learning with the PjBL model with Crossword media, this was proven through a t-test that obtained a value tcount > ttable (7.152 > 2,03452) with an N-gain value of 0.7079 (70.79%).